Pelatihan Manajemen Keuangan Kepada Para Bendahara Serikat Pekerja di Kota Batam - Prasetyo, Ary; Purwana Sari, Asih; Suratman, Suratman; Rina, Rina; Hanico, Andri; Afrinanda, Afrinanda; Hazriyanto, Hazriyanto (Institute for Research and Community Service (LPPM) of the Islamic University of Jember, 2024)
Abstract The financial management of the trade union in the context of organizational development is carried out independently, therefore it is necessary to understand good and correct financial management so that there is no misuse of the budget. Not many trade unions in Batam City have carried out good financial management. The implementation of this community service was carried out at Golden Prown, Bengkong, Batam City. The number of participants was the treasurers of the Management Unit of the Metal Electronic Workers Union of the All Indonesia Workers Union (PUK SP LEM SPSI) in Batam City, totaling 30 people. The method of implementing this community service was in the form of training on financial management of trade union organizations. The conclusion of this community service was that 97% of participants understood the material on financial management of the Workers Union. Abstrak Pengelolaan keuangan serikat pekerja dalam rangka pengembangan organisasi dilakukan secara mandiri oleh karena itu perlu memahami pengelolaan keuangan yang baik dan benar sehingga tidak terjadi penyalahgunaan anggaran. Serikat pekerja di kota Batam belum banyak yang melakukan menajemen keuangan dengan baik. Pelaksanaan pengabdian masyarakat ini dilaksanakan di Golden Prown, Bengkong, Kota Batam. Jumlah peserta yaitu para bendahara Pengurus Unit Kerja Serikat Pekerja Logam Elektronik Serikat Pekerja Seluruh Indonesia (PUK SP LEM SPSI) di kota Batam yang berjumlah 30 orang. Metode kegiatan pelaksanaan pengabdian masyarakat ini berupa pelatihan tentang manajemen keuangan organisasi serikat pekerja. Kesimpulan dari pengabdian masyarakat ini didapatkan hasil bahwa 97% peserta memahami materi tentang manajemen keuangan Serikat Pekerja.